Desulfovibrio Bacteria Are Associated With Parkinson’s Disease - Murros, Kari E.; Huynh, Vy A.; Takala, Timo M.; Saris, Per E. J. (Frontiers in Cellular and Infection Microbiology, 2021)
Parkinson’s disease (PD) is the most prevalent movement disorder known and predominantly affects the elderly. It is a progressive neurodegenerative disease wherein α-synuclein, a neuronal protein, aggregates to form toxic structures in nerve cells. The cause of Parkinson’s disease (PD) remains unknown. Intestinal dysfunction and changes in the gut microbiota, common symptoms of PD, are evidently linked to the pathogenesis of PD. Although a multitude of studies have investigated microbial etiologies of PD, the microbial role in disease progression remains unclear. Here, we show that Gram-negative sulfate-reducing bacteria of the genus Desulfovibrio may play a potential role in the development of PD. Conventional and quantitative real-time PCR analysis of feces from twenty PD patients and twenty healthy controls revealed that all PD patients harbored Desulfovibrio bacteria in their gut microbiota and these bacteria were present at higher levels in PD patients than in healthy controls. Additionally, the concentration of Desulfovibrio species correlated with the severity of PD. Desulfovibrio bacteria produce hydrogen sulfide and lipopolysaccharide, and several strains synthesize magnetite, all of which likely induce the oligomerization and aggregation of α-synuclein protein. The substances originating from Desulfovibrio bacteria likely take part in pathogenesis of PD. These findings may open new avenues for the treatment of PD and the identification of people at risk for developing PD.